Specific and General Beliefs in Union Voting Models - Deshpande, Satish P.; Fiorito, Jack (Academy of Management Journal, 1989)
Survey data have revealed that roughly three-fourths of nonunion employees view unions as effective in improving wages and working conditions, yet only about one-third would vote for unionization of their work place. This study illuminates the basis for that anomaly using theories about relations between the specificity of beliefs and behavioral intentions.